74 Pro-Angiogenic Effects of the Prolyl-hydroxylase Inhibitor FG-2216/BIQ: Therapeutic Angiogenesis for the Treatment of Chronic Total Occlusions. - Barnett, G; Schofield, C; Gershlick, A (2014)
: Percutaneous coronary intervention (PCI) is now the dominant revascularisation therapy for coronary artery disease, with nearly 3 million PCIs undertaken per annum world-wide. One of the last remaining challenges to PCI success is in cases of chronic total occlusions (CTO), where average UK success rates are around 66% (BCIS Data). It is only in the more experienced hands that success rates of 80-90% are achieved (EuroCTO club data).There is a need to develop alternative, effective therapies for CTO failures and to this end we have explored therapeutic angiogenesis to enhance antegrade collateral circulation and provide symptom relief in difficult CTO cases. We have investigated the stimulation of endothelial cell (EC) angiogenesis via stabilisation of hypoxia inducible factor (HIF) using two prolyl-hydroxylase inhibitors (PHI). We previously reported that di-methyl oxalylglycine (DMOG) loaded onto a polymer-coated stent increased collateral neovascularisation in a porcine CTO model. We now describe the actions of the PHI FG-2216/BIQ, which unlike DMOG has already been approved for use in man being trialled in patients with renal anaemia. Human umbilical vein endothelial cells (HUVECs) were cultured on growth factor reduced Matrigel in the presence of FG-2216 at a range of doses (from 0 to 500 μM). Endothelial cell (EC) tubule formation was measured at 6 h by image analysis of photomicrographs (image J). Western blotting was used to assess expression of HIF-1α in HUVEC after treatment with 500 μM FG-2216/BIQ for up to 24 h. Quantitative real time RT-PCR (qPCR) was used to examine the expression of vascular endothelial cell growth factor (VEGF) mRNA from treated HUVEC (up to 24 h). We report that as with DMOG, FG-2216 has a dose response, pro-angiogenic effect on HUVEC, with significantly enhanced tubule formation on Matrigel, compared to control (107 vs 21, p < 0.05) (Figure 1). Western blotting analysis of HUVEC protein demonstrated stabilisation of HIF-1α protein within 1-2 h of treatment with FG-2216, and qPCR results showed an increase in mRNA for the main angiogenic target of HIF-1α, vascular endothelial cell growth factor (VEGF). heartjnl;100/Suppl_3/A43-a/F1F1F1 Abstract 74 Figure 1 These proof of concept investigations confirm that FG-2216 has a pro-angiogenic effect in-vitro and is valid for testing in in-vivo models of CTO, with the potential for translation to man.We are currently developing novel strategies for the local, sustained delivery/release of FG-2216 such as drug eluting absorbable stenting and micro-sphere delivery as well as routine DES delivery to ensure slow release over long periods. These will be tested in the porcine CTO model developed by our group. We have a novel approach to perfusion by inducing therapeutic angiogenesis as an effective, innovative therapy for difficult CTO in man. Spin off therapies include peri-infarct ischaemia.